Transforming Social Guidance in Enhancing Community Collaboration for Sustainable Development - Betsi Siti Nurhidayah (P3M STAI Kuningan, 2024)
Background: Social guidance practices play a crucial role in fostering community collaboration for sustainable development. However, traditional approaches often fail to address the complex, dynamic nature of contemporary sustainability challenges. Understanding how transformed social guidance practices can enhance community collaborative capacity and contribute to sustainability outcomes remains underexplored in both theoretical and practical domains.Objective: This research examines the transformation of social guidance practices and their mechanisms in enhancing community collaboration for sustainable development, investigating the dimensions of transformed approaches, their operational mechanisms, and their impact on collaborative capacity and sustainability outcomes across diverse community contexts.Method: Employing a mixed-methods sequential explanatory design, the study investigates six purposively selected communities across urban, rural, and peri-urban contexts.Findings and Implications: The findings reveal five distinct dimensions characterizing transformed social guidance approaches: participatory orientation, adaptive learning, asset-based orientation, relational quality, and power-sharing. These transformation dimensions operate through multiple mechanisms—competence development, relationship formation, normative alignment, and institutional anchoring—to enhance collaborative capacity. Structural equation modeling indicates significant direct and mediated effects, with participatory orientation showing a standardized coefficient of 0.41 on collaborative capacity.Conclusion: The study contributes novel theoretical frameworks integrating insights from community development, sustainability science, and participatory governance literature. It generates practical implementation guidelines for development practitioners and policymakers seeking to catalyze community-driven sustainability transitions, demonstrating that transformed social guidance practices significantly enhance both collaborative capacity and measurable sustainability outcomes across diverse community contexts.